2020
DOI: 10.1111/hsc.13024
|View full text |Cite
|
Sign up to set email alerts
|

Assessing health science students' health literacy and its association with health behaviours

Abstract: Health literacy is an aspect of growing importance since it has been recognized as an important determinant for health status (Sun et al., 2013). Health literacy represents 'the cognitive and social skills which determine the motivation and ability of individuals to gain access to, understand and use information in ways which promote and maintain good health' (Smith, Tang, & Nutbeam, 2006). According to the European Health Literacy Project (HLS-EU) it is the achievement of 'knowledge, motivation and competence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 27 publications
(47 reference statements)
1
15
1
8
Order By: Relevance
“…We also investigated the relationships between health literacy and all HPLP-II domains. In a previous study conducted with health science students, only physical activity and health responsibility HPLP-II domains were related to health literacy [49], but in the current study, health literacy is positively associated with all sub-domains of HPLP-II. This finding suggests that improved health literacy can lead to a range of improvements in health status, including physical, mental, and spiritual health.…”
Section: Discussioncontrasting
confidence: 79%
“…We also investigated the relationships between health literacy and all HPLP-II domains. In a previous study conducted with health science students, only physical activity and health responsibility HPLP-II domains were related to health literacy [49], but in the current study, health literacy is positively associated with all sub-domains of HPLP-II. This finding suggests that improved health literacy can lead to a range of improvements in health status, including physical, mental, and spiritual health.…”
Section: Discussioncontrasting
confidence: 79%
“…As a result of the generalization of theoretical knowledge, own practical experience of research [17,18,19] and specialists using diagnostic models for assessing the health level of students, simple, affordable methods for assessing the level of health are selected, the use of which does not create any organizational and technical difficulties in the process of mass research.…”
Section: Methodsmentioning
confidence: 99%
“…As early as 1974, Simonds (6) had pointed out that improving HL should be an important component of public social policy. Studies from multiple countries have shown that low HL negatively affects health, health-related and illness-related behavior, and the utilization of health care resources (7)(8)(9)(10)(11). Currently, HL is still low in many countries.…”
Section: Introductionmentioning
confidence: 99%